Origin of silica, paleoenvironment, and organic matter enrichment in the Lower Paleozoic Niutitang and Longmaxi formations of the northwestern Upper Yangtze Plate: Significance for hydrocarbon exploration. (May 2019) - Li, Delu; Li, Rongxi; Tan, Chengqian; Zhao, Di; Xue, Tao; Zhao, Bangsheng; Khaled, Ahmed; Liu, Futian; Xu, Feng
Abstract: Lower Paleozoic shale is an important source rock and reservoir for gas in the northwestern Upper Yangtze Plate. The paleoenvironment, and its impact on organic matter enrichment of the shale, plays a vital role in the exploration and development of the resource. Based on the analysis of the results of total organic carbon (TOC), maceral examination, bitumen reflectance (Rb), major elements, trace elements, rare earth elements (REEs), and X-ray diffraction (XRD) of shale samples from the Niutitang and Longmaxi formations, the origin of silica, the paleoenvironment, and the mode of organic matter enrichment of the shale were examined. The shales of the Niutitang and Longmaxi formations have high TOC abundance, with Type I organic matter and high maturity. Quartz and clay minerals dominate the mineral constituents, leading to characterization as siliceous shale. The average SiO2 content of the shale in the Niutitang and Longmaxi formations is above 70 wt%. Al2 O3 and TFe2 O3 (total iron) are the next-most abundant major elements, with average values of 12.80 wt% and 1.95 wt% in the Niutitang Formation, and average values of 11.44 wt% and 4.09 wt% in the Longmaxi Formation. Compared with the Upper Continental Crust (UCC), V, Mo and U are the most enriched elements. The average ∑LREE/∑HREE of the shale samples is very low, and the Chondrite-normalized REE distribution pattern shows sloping LREE trends and flat HREE trends towards the right. The total rare earth elements of the shale vary within the range of 147.85–219.60 ppm and 159.90–222.02 ppm in both the Niutitang and Longmaxi formations, suggesting that the shale has not been subject to obvious hydrothermal fluid activities. The correlation diagrams of SiO2 Al2 O3, SiO2 -TOC and Siexcess -TOC, the diagrams of hydrothermal origins, and the elemental parameters indicate that the silica of the shales from the Niutitang and Longmaxi formations are mainly of biogenic origins, with a lesser contribution from terrigenous detrital sources. The ratios of MnO2 /TiO2 and Al2 O3 /(Al2 O3 +TFe2 O3 ) of the shale samples all show limited variability, illustrating that the shales are mainly deposited on the continental margin. The average chemical alteration index (CIA) values of the Niutitang and Longmaxi formations are 71.25 and 72.77 with little variation, and the average Sr/Cu ratios are 4.38 and 2.22, reflecting a warm and humid paleoclimate for both formations. The average Ni/Co, Th/U, and δU readings of the shale samples of the formations are 10.91, 0.97 and 1.51, and 12.69, 0.43 and 1.75, indicating that the redox conditions during the sedimentation of the formations were anoxic. The positive correlations between TOC and paleoenvironmental proxies reveal a warm and humid climate, and that anoxia had a positive effect on organic matter enrichment. These conditions have laid a geological foundation for the enrichment of shale gas, and that the Upper Yangtze Plate is favorable for future shale gas exploration. Highlights: The shales of Niutitang Formation and Longmaxi Formation are both good source rocks. The silica origin of the shales is primarily biogenic. The shales were deposited in warm and humid climate with anoxic condition. The paleoclimate and anoxic conditions had a positive effect on OM accumulation.